Violence and genocide in African literature and film - Vambe, Maurice Taonezvi; Rwafa, Urther (UNISA Press, 2021)
Studies on violence and genocide in Africa have for many years relied on the disciplines of history, sociology, and individual testimonies to make sense of the crimes against humanity. The main justification for using anthropological and sociological accounts to explain violence and genocide in Africa has been encouraged by an empiricist research culture that relied on quantitative methods to measure the impact of violence and genocide in Africa. The main aim in these sorts of research had been to over-awe the world with the image of Africa as the heart of darkness. These approaches are forcefully recreated in the worked by critics like Patrick Chabal and Jean-Pascal (1999) for whom it is disorder that makes Africa work. Furthermore the reliance on the evidence provided in statistics gathered from the victims who of violence and genocide unfortunately was manipulated by some critics to create the wrong perception which that only the people in Africa affected directly by violence and genocide could write insightfully and authoritatively on the subject. These views have now been challenged in a new scholarship by young African intellectuals. These African intellectuals as are represented in this issue argue in different ways that the structural, systemic and symbolical forms of violence introduced by colonialism, found a new life and was and then intensified by some postcolonial leaders whose politics undermined the potential of Africa to grow out of the stereotype constituted in the view that the continent is a place where anything and everything negative that can happen in the world is manifested. The power of the voices of victims of genocide has also provided compelling evidence of, and provided a robust moral argument to convince the world to act whenever the spectre of genocidal wars rears its head. But the actions of the world’s powerful governments have been selective. Where their interests lay, they would act or not act depending on the global coalition forces’ immediate interests. There is however in Africa, a refreshing look by young African intellectuals that refuse to minimize the complicity of Africans in their own historical misfortunes.